Mathematics

Question

Simplify write equivalent expressions. 4-2+(3b+6)

2 Answer

  • The first thing you want to do in this equation is get rid of the parenthesis. Because 4-2 is added to (3b+6) you cannot distribute the 2. However, there is an invisible 1 next to the parenthesis, so you can use that. Additionally, I like to change subtraction to addition of a negative number. It makes things a little less confusing.

    4+ -2 + 3b + 6

    Now just combine the like terms.

    4 + -2 = 2
    6+ 2 = 8

    So the simplified version of your problem is: 3b + 8
  • 4- 2+ (3b+6)
    = 2+ 3b+ 6
    = 3b + (2+6)
    = 3b+ 8

    Hope this helps~
NEWS TODAY